1970
DOI: 10.22270/ajprd.v7i3.510
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Effect of the Voice of the Holy Quran and Arendeshine Music on the Anxiety of the Primiparous Women of the Natural Provisional Candidate

Abstract: Introduction and goal: Anxiety is the most common psychological reaction of pregnant women near childbirth and is a high prevalence in Iranian women. Nearly 50% of pregnant women report high levels of anxiety. The use of pharmaceutical methods to solve this problem has always led to problems and complications for patients. One of the non-pharmacological methods of music therapy. Therefore, the present study was conducted to compare the effects of the Voice of the Holy Qur'an and Arendeshine music on the anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
7
0
3
Order By: Relevance
“…By backword reference list checking, three additional studies were found and added to this review. Overall, 11 studies were included in a narrative synthesis [29][30][31][32][33][34][35][36][37][38][39], and 7 of those studies were included in a meta-analysis [29-31, 34, 35, 37, 38].…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…By backword reference list checking, three additional studies were found and added to this review. Overall, 11 studies were included in a narrative synthesis [29][30][31][32][33][34][35][36][37][38][39], and 7 of those studies were included in a meta-analysis [29-31, 34, 35, 37, 38].…”
Section: Search Resultsmentioning
confidence: 99%
“…Eight studies examined the effect of listening to the Quran on anxiety [29,30,[33][34][35][36][37][38]. While six of these studies were conducted in Iran [29,30,[35][36][37][38], the remaining two studies were carried out in Tunisia [33] and Indonesia [34].…”
Section: Anxietymentioning
confidence: 99%
See 3 more Smart Citations